Inhibition of activator protein 1 signaling abrogates transforming growth factor β-mediated activation of fibroblasts and prevents experimental fibrosis - Avouac, Jerome; Palumbo, Katrin; Tomcik, Michal; Zerr, Pawel; Dees, Clara; Horn, Angelika; Maurer, Britta; Akhmetshina, Alfiya; Beyer, Christian; Sadowski, Anika; Schneider, Holm; Shiozawa, Shunichi; et al. (Arthritis and Rheumatism, 2012)
Objective To investigate whether c-Jun and c-Fos contribute to the pathologic activation of fibroblasts in systemic sclerosis (SSc) and to evaluate the antifibrotic potential of selective activator protein 1 (AP-1) inhibition. Methods Expression of c-Jun and c-Fos was determined by real-time polymerase chain reaction (PCR) and immunohistochemical analysis. Fibroblasts were stimulated with transforming growth factor β (TGFβ) and incubated with T-5224, a small-molecule inhibitor of AP-1, or were transfected with small interfering RNA (siRNA) duplexes against c-Jun and c-Fos. Collagen synthesis was quantified by real-time PCR and hydroxyproline assay. Differentiation of resting fibroblasts into myofibroblasts was assessed by staining for α-smooth muscle actin and stress fibers. The antifibrotic potential of T-5224 was evaluated in mouse models of dermal fibrosis induced by bleomycin or by adenoviral overexpression of a constitutively active TGFβ receptor type I. Results Up-regulation of c-Jun and c-Fos was detected in mouse models of SSc and in the skin and dermal fibroblasts of patients with SSc. Stimulation of healthy fibroblasts with TGFβ induced the expression of c-Jun and c-Fos. Treatment with T-5224 or nucleofection with siRNA directed against c-Jun and c-Fos abrogated the profibrotic effects of TGFβ. T-5224 decreased the release of collagen selectively in SSc fibroblasts. T-5224 was well tolerated and prevented dermal fibrosis induced by bleomycin or by adenoviral activation of TGFβ signaling. Conclusion AP-1 is up-regulated in a TGFβ-dependent manner in SSc. The selective AP-1 inhibitor T-5224 reduced collagen synthesis selectively in SSc fibroblasts and efficiently prevented the development of experimental dermal fibrosis. Thus, AP-1 might be a promising new molecular target for the treatment of SSc. Copyright © 2012 by the American College of Rheumatology.
CRIS-Team Scopus Importer:2020-07-01